The effects of anion deposition and negative pulse on the behaviours of plasma electrolytic oxidation (PEO)—A systematic study of the PEO of a Zirlo alloy in aluminate electrolytes. (20th January 2017) - Cheng, Yingliang; Wang, Ting; Li, Shaoxian; Cheng, Yulin; Cao, Jinhui; Xie, Huanjun
Graphical abstract: Highlights: PEO of a Zirlo alloy in aluminate electrolytes under different electrical regimes. PEO was systematically characterized by SEM, EDS and OES. Anion deposition process significantly affects PEO behaviours. Hydrogen evolution during negative pulse facilitates anion deposition. Anion deposition in PEO differs from that in conventional anodizing. Abstract: Plasma electrolytic oxidation (PEO) of a Zirlo alloy has been carried out under pulsed bipolar and pulsed unipolar regimes in aluminate electrolytes with the aim to promote a better understanding of the coating formation mechanisms and the role of negative pulse. Real time imaging, optical emission spectroscopy (OES), gas collection, scanning electron microscopy (SEM) assisted with energy dispersive X-ray spectroscopy (EDS) and X-ray diffraction (XRD) have been used to characterize the PEO processes and the resultant coatings. The results show that the anion deposition process has significantly affected the composition, microstructure of the coatings and the plasma discharge behaviour. For the coatings formed with less incorporation from the electrolyte anions, the predominant discharge type is the energetic penetrating discharges, usually forming the pancake structure and big internal pores. However, the formation of coatings by the fast deposition of anion species with the assistance of "soft sparking" or "sintering arcs" occurs when PEO was carried out in concentrated electrolytes. The occurrence of such discharges is correlated with the fact that less energy is required for the anion deposition process. The hydrogen evolution associated with the negative pulse during PEO can promoted the transportation of electrolyte species to the electrode surface, favoring the formation of homogenous coatings with the incorporation of more electrolyte species and a modified discharge types.